PENGARUH PIJAT EFFELEURAGE TERHADAP NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI WILAYAH PUSKESMAS LANDASAN ULIN KOTA BANJARBARU TAHUN 2025 - Anita Syafarina; Isnaniah; Erni Yuliastuti; Efi Kristiana (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Background: Back pain is a common musculoskeletal complaint experienced by third-trimester pregnant women due to physiological and hormonal changes as well as increased mechanical load on the spine. Effleurage massage is a non pharmacological technique that provides relaxation effects, improves blood circulation, and reduces muscle tension, thereby potentially decreasing back pain. Objective: To determine the effect of effleurage massage on back pain among third trimester pregnant women in the working area of Landasan Ulin Public Health Center, Banjarbaru City, in 2025. Methods: This study employed a one-group pretest–posttest design with a sample of 30 third-trimester pregnant women selected using purposive sampling. Pain intensity was measured using the Numeric Rating Scale (NRS). Data analysis was conducted using the Paired Sample T-Test to examine differences in pain levels before and after the intervention. Results: Prior to the intervention, respondents experienced moderate pain (46.67%) and severe pain (33.33%). After the intervention, pain levels decreased to mild pain (63.33%) and no pain (6.67%). The Paired Sample T-Test showed a p-value of < 0.001, indicating a statistically significant effect of effleurage massage on the reduction of back pain. Conclusion: Effleurage massage has a significant effect on reducing back pain in third-trimester pregnant women and can be recommended as a non-pharmacological intervention in antenatal care services.